GAMBARAN EPIDEMIOLOGI FAKTOR RISIKO PREEKLAMSIA PADA IBU HAMIL - ika primayanti; Ario Danianto; Rizkinov Jumsa; NN Geriputri; Marie Yuni Andari (Faculty of Medicine Universitas Mataram, 2022)
Preeclampsia is one of the main causes of maternal death in addition to bleeding and infection. The increasing incidence of preeclampsia is of course a problem amid increasing efforts to provide maternal health services. Risk factors for the incidence of preeclampsia can be found through history assessment and special examinations at antenatal care. Through early detection of risk factors for preeclampsia, it is hoped that maternal and perinatal morbidity and mortality can be prevented. This study aims to identify in order to obtain an epidemiological description of the risk factors for the incidence of preeclampsia in pregnant women. The research design was descriptive observational with cross sectional approach. The research data were obtained from interviews, KIA’s book, accompanied by blood pressure checks and proteinuria examinations through a simple dip test of second trimester pregnant women who underwent antenatal care in July - November 2021 About 52 sample have been taken by purposive sampling technique. Obtained 8 of 9 moderate risk factors for preeclampsia in respondents with the most factor being Mean Arterial Pressure (MAP) >90mmHg about 17 respondents (32.7%) while in high risk factors for preeclampsia where the most factor is a history of chronic hypertension namely 2 respondents (3.8%).